Perception about pap smear screening test among females attending a tertiary care center - Shantha, A.; Somu, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Knowledge regarding the screening test (Pap smear) among women has been proven to be a significant predictor of first-time screening and in turn helps in early diagnosis and treatment of the disease. Hence this study was conducted to assess the knowledge and practice of pap smear screening test for cervical cancer among the women attending the outpatient department of obstetrics and gynecology. Methods: The cross-sectional study was conducted by the department of obstetrics and gynecology, at Sri Muthukumaran Medical College Hospital and Research Institute, among the women attending the outpatient department, during the month of August 2019. A total of 180 participants were included in the study. Data was entered in Microsoft excel and data analysis was done using statistical package for social sciences (SPSS) version 17. Results: Knowledge about carcinoma cervix and pap smear were present among 86.7% and 74.4% of participants, respectively. About the practice of pap smear, only 24.4% of the study participant have undergone the screening test and only two participants had taken the HPV vaccine. Conclusions: Most of the women had poor attitude and practice related to screening and vaccination for cervical cancer. But their attitude is favorable for screening. Hence promotion of free regular health check-up and vaccination for cervical cancer among general population might increase the awareness and decrease the disease burden.